Urine Drug Screening for a History of Isolated Marijuana Use: Is Our Help Hurting? [A224]. (May 2022) - Rubin, Alexandra; Zhong, Lydia; Nacke, Lauren; Raghuraman, Nandini; Carter, Ebony B.; Kelly, Jeannie
Abstract : INTRODUCTION: Despite being widely legalized, marijuana use commonly triggers urine drug screening (UDS) in obstetric practice, mainly to identify other substance exposures that could require intervention. We sought to identify frequency of concomitant nonprescribed substance use in patients who underwent UDS for isolated marijuana use (IMU) at delivery. METHODS: We performed a retrospective cohort study of all patients admitted for delivery from January 1 to July 31, 2020, at an urban academic center where UDS are sent based on specific criteria, including IMU. Demographic data were compared between those with IMU versus those not meeting UDS criteria. UDS results for patients with IMU are described. RESULTS: Of 2, 045 deliveries, 484 (23.7%) had UDS performed. Reported IMU represented the most common reason for UDS (43.2%). Compared to patients who did not meet UDS criteria, those undergoing UDS for IMU were more likely Black (78.5% versus 43.1%, P <.001), younger (median age 25 versus 29 years, P <.001), and publicly insured (60.9% versus 37.0%, P <.001). Of 209 UDS sent for IMU, 4 (1.9%) were positive for nonprescribed substances other than marijuana. Of 125 UDS positive for marijuana only, 117 (93.6%) were mandatorily reported to the state Child Abuse/Neglect hotline. All 209 (100%) patients with IMU were discharged home with their infant. CONCLUSION: Over 40% of UDS were sent due to IMU on a labor unit, but ultimately identified a minority of other substance exposures. IMU as an indication for UDS disproportionately targets young, Black, publicly insured patients by triggering a downstream cascade of stigmatized legal consequences, and should be carefully examined for necessity.